Improving the information security sustainability of the economy financial sector - V. V. Kachurin; R. G. Akhmadeev (Вестник университета)
The legal certainty of the legislative acts in force in the Russian Federation concerning the organizational and legal basis for countering the funds laundering of criminal origin and clear regulation of the financial monitoring procedure, as well as the interaction of authorities are fundamental elements for the purpose of financial control. At the same time, countering the money laundering is a global aspect that directly affects both society and the economic system of most economically developed countries. The study analyzes the main activities of Russia Bank, aimed at ensuring the sustainability of information security in the financial sector of the economy, as well as ongoing activities aimed at limiting the spread of cybercrime based on an automated incident handling system. In order to solve strategic tasks in the financial security field of market entities, practical recommendations are proposed to improve the mechanism of countering to cyber crimes on the basis of financial monitoring of acquiring operations and corporate bank cards.